Screening Of Α-Glucosidase Inhibitors From Black Soybean Extract And Study On Their Inhibitory Mechanisms - Zheng, Yu (2024)
Various studies have documented the beneficial effects of black soybean extract against diabetes. However, the specific active compounds responsible for these effects remain elusive. This study aimed at identifying the α-glucosidase inhibitors present in black soybeans using affinity ultrafiltration. Seven isoflavones with α-glucosidase inhibitory activity were identified, among which daidzein and genistein demonstrated remarkably superior inhibitory activity compared to that of acarbose (IC50 = 632.5 ± 70.0 μmol/mL), exhibiting IC50 values of 15.7 ± 0.3 and 3.2 ± 1.2 μmol/mL, respectively. An analysis of the structure-activity relationship revealed a negative correlation between the degree of glycosylation of isoflavone and α-glucosidase inhibitory activity. Enzyme kinetic studies revealed that both daidzein and genistein acted as uncompetitive inhibitors of α-glucosidase. Additionally, these compounds effectively suppressed the intrinsic fluorescence of α-glucosidase through the static quenching mechanism. The interaction between daidzein or genistein and α-glucosidase involves spontaneous formation of a complex, which is driven by hydrophobic interactions and hydrogen bonds. These findings provide valuable insights into the molecular mechanisms underlying the α-glucosidase inhibitory activity of black soybean isoflavones.